2011
DOI: 10.1039/c1sm06550e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Fmoc-tetrapeptides based on the RGDS cell adhesion motif

Abstract: Self-assembly in aqueous solution has been investigated for two Fmoc [Fmoc = N-(fluorenyl)-9-methoxycarbonyl] tetrapeptides comprising the RGDS cell adhesion motif from fibronectin or the scrambled sequence GRDS. The hydrophobic Fmoc unit confers amphiphilicity on the molecules, and introduces aromatic stacking interactions. Circular dichroism and FTIR spectroscopy show that the self-assembly of both peptides at low concentration is dominated by interactions among Fmoc units, although Fmoc-GRDS shows β-sheet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 68 publications
7
72
0
Order By: Relevance
“…Fibril structures were found in both cases and entanglement of fibers was also observed, which is consistent with reported literature. 27 In presence of Fmoc-RGDS-AAP, SEM showed more cross-linking fibers (Fig. 3) compared to only Fmoc-RGDS (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Fibril structures were found in both cases and entanglement of fibers was also observed, which is consistent with reported literature. 27 In presence of Fmoc-RGDS-AAP, SEM showed more cross-linking fibers (Fig. 3) compared to only Fmoc-RGDS (Fig.…”
mentioning
confidence: 99%
“…It has been reported that Fmoc-RGDS can form hydrogel and serve as cell adhesion motif. 27 The p-p interaction between hydrophobic…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…group being highly hydrophobic due to the presence of t-butyl carbamate group that is involved in hydrophobic interactions, allowing for the formation of gelatinous structures in aqueous solution [42][43]. Additionally, the presence of amide bonds allow for H-bonding interactions similar to natural peptide backbone between the -NH and C=O groups.…”
Section: Formation Of Fvbs Assembliesmentioning
confidence: 99%